Moderate grade subglottic stenosis in children: Laryngotracheal reconstruction versus cricotracheal resection and anastomosis - Beatrix Christina Kokje, Vivianne; Ishii, Alessandro; Sandu, Kishore (Frontiers in Pediatrics, 2022)
Objective The surgical treatment of choice of pediatric moderate subglottic stenosis (major grade II and minor grade III SGS or 60-80% lumen obstruction) remains controversial. Laryngo-tracheal reconstruction (LTR) (with anterior +/- posterior grafts for airway expansion) and partial crico-tracheal resection (PCTR) are the main described open surgical techniques. We reviewed our pediatric cases with moderate subglottic stenosis to determine the efficacy of LTR versus PCTR. Methods A retrospective study of all children between 0 and 18 years that underwent open reconstructive airway surgery between 2012 and 2019. Children who had either acquired or congenital moderate subglottic stenosis (late grade II and early grade III: 60-80% lumen obstruction) were selected. Results Twenty-six children with moderate grade subglottic stenosis were included. Seventeen were treated with LTR and nine with PCTR. No significant differences were observed between LTR and PCTR treated cases. Decannulation rates were similar, as well as the functional results. Conclusion Both LTR and PCTR are valid treatment options for moderate subglottic stenosis. This study indicates to perform the surgery that is most suitable for the characteristics of the patients’ stenosis, the surgeons’ expertise and preference and the working infrastructure.